2016
DOI: 10.1093/jxb/erw368
|View full text |Cite
|
Sign up to set email alerts
|

Characterising root trait variability in chickpea (Cicer arietinumL.) germplasm

Abstract: HighlightLarge variation in root system architecture in chickpea germplasm was identified across 270 genotypes, providing information that can be used in developing genotypes with root traits for improved adaptation to specific environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 53 publications
5
83
0
3
Order By: Relevance
“…The large genotypic variation in root morphology observed in the 100 chickpea genotypes when grown under low‐P conditions in our study, is consistent with the results of Chen et al . (), who found large variation in rooting patterns among 270 chickpea genotypes grown in semi‐hydroponics system with optimum supply of all nutrients. Likewise, significant genotypic differences in root length and root hair length were found among 10 chickpea genotypes (Gahoonia et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large genotypic variation in root morphology observed in the 100 chickpea genotypes when grown under low‐P conditions in our study, is consistent with the results of Chen et al . (), who found large variation in rooting patterns among 270 chickpea genotypes grown in semi‐hydroponics system with optimum supply of all nutrients. Likewise, significant genotypic differences in root length and root hair length were found among 10 chickpea genotypes (Gahoonia et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Information on these genotypes, including country of origin, biological status (advanced cultivar, breeding material and landrace) and seed type (desi, kabuli or pea‐shaped) are described in Chen et al . () and Atieno et al . ().…”
Section: Methodsmentioning
confidence: 97%
“…It has been observed in several crop species that large diversity exists for root characteristics through the use of different root phenotyping methods (Nakamoto et al, 1991;Manschadi et al, 2006Manschadi et al, , 2008Chen et al, 2016). These authors came to the conclusions that the plasticity of root architecture increases adaptability, which in turn should improve productivity when the best fit is deployed for specific soils and moisture conditions.…”
Section: Field Variation For Grain Size Based On Differences In Root mentioning
confidence: 99%
“…This study revealed the important role of root metaxylem in water use efficiency and stomatal conductance during the reproductive stage of plant development and that root metaxylem number was associated with soybean lines that produced high yields under drought stress (Prince et al, ). Root trait phenotyping across a large germplasm collection is important to identify candidate genotypes with suitable root traits for breeding of new varieties through marker‐assisted selection programmes and QTL mapping (Chen et al, ).…”
Section: Legume Genetic Resources Under Environmental Stressesmentioning
confidence: 99%